Study of Asphalt Pavement Cracking in Different Road Sections of Morocco Using Electrical Resistivity Tomography - Khalid Krami; Ahmed Benamara; Mohammed Radouani; Mohammad Ettayeb; Lhoussaine Tarik (International Journal of Geophysics)
Road pavements undergo various environmental factors such as temperature changes, precipitation, and traffic exposure, which can lead to cracks in asphalt pavements compromising road user safety and necessitating costly repairs. To gain a deeper understanding of the mechanisms behind asphalt pavement cracking, this study proposes the utilization of the electrical resistivity tomography method to measure the electrical resistivity of soil-supporting road pavements. Electrical resistivity measurements were conducted on soil-supporting road pavements at various times, both before and during the winter season, in four different road sections. Two of these sections were located on Regional Road N707 in the Ifrane region, while the other two were located on National Road N13 in the Azrou and Timahdite regions. The results of the geophysical campaign provided valuable insights into the impact of the winter season on soil resistance and the formation of cracks in asphalt pavements. To achieve this, electrical tomography was employed to generate 2D images of the electrical resistivity of the soil, which were subsequently compared to asphalt cracking data collected in the field through visual surveys and/or asphalt cores. The 2D analysis of the electrical resistivity images of the road pavements under study revealed a decrease in electrical resistivity values during the winter season. This decrease can be attributed to a combination of factors including asphalt pavement cracking, water infiltration during winter, and soil characteristics supporting the asphalt pavement. These findings offer valuable insights intro targeted maintenance and repair efforts.